2019
DOI: 10.5271/sjweh.3827
|View full text |Cite
|
Sign up to set email alerts
|

Correction of bias in self-reported sitting time among office workers – a study based on compositional data analysis

Abstract: Correction of bias in self-reported sitting time among office workers -a study based on compositional data analysis by Coenen P, Mathiassen SE, van der Beek AJ, Hallman DM Being the first to develop a calibration model using compositional data analysis, we found that a model in which "true" occupational sitting was estimated from self-reported sitting, or even additional predictors, led to substantially more correct estimates than if only self-reports were used. Our models can be used for post-hoc improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…nutritional epidemiology ( Leite, 2016 ), geology ( Tolosana-Delgado and von Eynatten, 2009 ), and chemistry ( Buccianti and Pawlowsky-Glahn, 2005 ). However, in public and occupational health sciences, CoDA has gained attention only recently ( Pedišić, 2014 ; Chastin et al , 2015 ; Pedisic et al , 2017 ; Dumuid et al , 2018b ; Foley et al , 2018 ; Bauman et al , 2019 ), with few papers devoted to exposures at work ( Gupta et al , 2018a , 2019 ; Rasmussen et al , 2018 ; Hallman et al , 2019 ; Coenen et al , 2020 ).…”
Section: Time Use In Occupational Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…nutritional epidemiology ( Leite, 2016 ), geology ( Tolosana-Delgado and von Eynatten, 2009 ), and chemistry ( Buccianti and Pawlowsky-Glahn, 2005 ). However, in public and occupational health sciences, CoDA has gained attention only recently ( Pedišić, 2014 ; Chastin et al , 2015 ; Pedisic et al , 2017 ; Dumuid et al , 2018b ; Foley et al , 2018 ; Bauman et al , 2019 ), with few papers devoted to exposures at work ( Gupta et al , 2018a , 2019 ; Rasmussen et al , 2018 ; Hallman et al , 2019 ; Coenen et al , 2020 ).…”
Section: Time Use In Occupational Researchmentioning
confidence: 99%
“…too little non-sitting ( van der Ploeg and Hillsdon, 2017 ; Stamatakis et al , 2019 ). Analyzing compositional data using standard methods may even in some cases lead to absurd results, such as confidence intervals (CIs) including values less than 0% or more than 100% time ( Coenen et al , 2020 ).…”
Section: The Whys Of Codamentioning
confidence: 99%
See 1 more Smart Citation
“…A novelty of this study is the use of the complete composition of multiple self-reported physical behaviors to predict ‘true’ time use. In a previous calibration study in the same population, we focused only on sitting [35] and expressed sitting time using a single ILR (i.e., sit/nonsit) without considering that self-reported information on behaviors occurring during non-sitting (i.e., standing and walking) might be of additional predictive value for sitting. In that study, we found that the simple calibration model reduced RMS error for the sit/nonsit ILR to 55% of the error before calibration.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that calibration within a CoDA framework can be effective in improving the accuracy of self-reported time in a single behavior (sitting) among office workers [35]. It is likely that calibration of a particular behavior will be even more effective, that is, lead to more accurate estimates of ‘true’ behavior, if self-reports of all other component behaviors are also included as predictors.…”
Section: Introductionmentioning
confidence: 99%